How to make a multilayer pie chart in Excel (Karina Adcock, 2021)
Create a multilevel donut chart in excel ——————————————————————————– # exceltips #exceltutorials #excelcharts SUBSCRIBE: https://goo.gl/c46YP s Microsoft Office 365, Beta Channel, Version 2104 ——————————————————— ———————— IF YOU LIKED THIS VIDEO YOU MAY ALSO LIKE: - Recreating a pie chart from a newspaper in PowerPoint    • How to make a pie...